Penegakan Hukum Pidana Terhadap Penyelundupan Satwa yang Dilindungi - I Wayan Suja; Ida Ayu Sadnyini (LPPM Universitas Ekasakti Padang, 2023)
The government protects animals that need to be safeguarded. Which in this situation means that people are not permitted to perform acts that are contrary to the norms established by the government, in this case with regard to protected animals. Article 1 point 1 of Law No. 5 of 1990 concerning Conservation of Natural Resources states that animals that develop and dwell on land, in the air, or in water and have various natural characteristics are considered separate creatures, including those that are managed by people or that are found in the wild. The formulation in this study is as follows how is the legal regulation of animal smuggling and how are criminal sanctions against animal smuggling. The method used is a method of normative legal research. It is expected that the government and the people of Indonesia, in particular, to be willing to participate in protecting and eradicating people in terms of hunting protected wild animals, where it aims to keep rare animals around us sustainable